Twiggy : A Guide to Looking and Feeling Fabulous Over Forty - Twiggy and Dyson, Jenny; Illustration by Berning, Tina (London Michael Joseph, 2008)
When we reach our forties, something changes. Suddenly nothing - hair, skin, body shape - looks quite the way it used to. Nothing can stop the ageing process. Why shouldn't forty, fifty or sixty be as beautiful as twenty or thirty in a different way? This guide helps you with hundreds of tips
Include Color Illustration
Keywords: Middle-aged women--Health and hygiene -- Beauty, Personal